2019
DOI: 10.1186/s42358-019-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound inflammatory parameters and Treg/Th17 cell profiles in established rheumatoid arthritis

Abstract: Background: Imbalance and disfuntion in regulatory T-cells (Tregs) and IL-17 producer lymphocytes (Th17) have been implicated in the pathogenesis of rheumatoid arthritis (RA). Gray scale synovial proliferation (GS), power Doppler signal (pD) and bone erosions seen on high resolution muskuloskeletal ultrasound (MSUS) are hallmarks of destructive articular disease. Objective: To evaluate the association of peripheral Tregs and Th17 with MSUS findings in RA. Methods: RA patients (1987 ACR criteria) treated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In recent years, bone immune regulation has become a hot topic in research on bone metabolic diseases ( 74 ). Research has found that bone immunity has a destructive effect ( 75 ), and bone immune disorders induced by Th17 cells, Tregs, and related cytokines are important triggers for the development of RA and PMOP ( 17 , 76 ) Many studies have shown that the proportion of Th17 cells in the serum and synovium of patients with RA and collagen-induced arthritis (CIA) rats is far higher than that of Treg cells, however, inhibiting Th17 cells and upregulating Treg cells can alleviate arthritis and bone destruction ( 77 , 78 ), indicating that regulating the Th17/Treg cell balance may be important for the treatment of RA. In addition, some studies have confirmed that in patients with PMOP and ovariectomized (OVX) mice, Th17 cells and their related cytokines, such as IL-17, TNF-α, and IL-6, increased, Treg cells and their related anti-inflammatory factors decreased, OC-mediated bone resorption and OB-mediated bone formation were out of balance, the Th17/Treg ratio increased, and the bone remodelling process was worsened.…”
Section: Relationship Between Th17/treg Imbalance and Rheumatoid Arth...mentioning
confidence: 99%
“…In recent years, bone immune regulation has become a hot topic in research on bone metabolic diseases ( 74 ). Research has found that bone immunity has a destructive effect ( 75 ), and bone immune disorders induced by Th17 cells, Tregs, and related cytokines are important triggers for the development of RA and PMOP ( 17 , 76 ) Many studies have shown that the proportion of Th17 cells in the serum and synovium of patients with RA and collagen-induced arthritis (CIA) rats is far higher than that of Treg cells, however, inhibiting Th17 cells and upregulating Treg cells can alleviate arthritis and bone destruction ( 77 , 78 ), indicating that regulating the Th17/Treg cell balance may be important for the treatment of RA. In addition, some studies have confirmed that in patients with PMOP and ovariectomized (OVX) mice, Th17 cells and their related cytokines, such as IL-17, TNF-α, and IL-6, increased, Treg cells and their related anti-inflammatory factors decreased, OC-mediated bone resorption and OB-mediated bone formation were out of balance, the Th17/Treg ratio increased, and the bone remodelling process was worsened.…”
Section: Relationship Between Th17/treg Imbalance and Rheumatoid Arth...mentioning
confidence: 99%